Elucidation of the mechanism of redox grafting of diazotated anthraquinone - Chernyy, Sergey (Langmuir : the ACS journal of surfaces and colloids, 2012)
Redox grafting of aryldiazonium salts containing redox units may be used to form exceptionally thick covalently attached conducting films, even in the micrometers range, in a controlled manner on glassy carbon and gold substrates. With the objective to investigate the mechanism of this process in detail, 1-anthraquinone (AQ) redox units were immobilized on these substrates by electroreduction of 9,10-dioxo-9,10-dihydroanthracene-1-diazonium tetrafluoroborate. Electrochemical quartz crystal microbalance was employed to follow the grafting process during a cyclic voltammetric sweep by recording the frequency change. The redox grafting is shown to have two mass gain regions/phases: an irreversible one due to the addition of AQ units to the substrate/film and a reversible one due to the association of cations from the supporting electrolyte with the AQ radical anions formed during the sweeping process. Scanning electrochemical microscopy was used to study the relationship between the conductivity of the film and the charging level of the AQ redox units in the grafted film. For that purpose, approach curves were recorded at a platinum ultramicroelectrode for AQ-containing films on gold and glassy carbon surfaces using the ferro/ferricyanide redox system as redox probe. It is concluded that the film growth has its origin in electron transfer processes occurring through the layer mediated by the redox moieties embedded in the organic film